2020
DOI: 10.1155/2020/6325490
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Open-Label One-Arm Trial Investigating a Pumpkin Seed, Isoflavonoids, and Cranberry Mix in Lower Urinary Tract Symptoms/Benign Prostatic Hyperplasia: A Pilot Study

Abstract: Phytotherapy for lower urinary tract symptoms (LUTSs) due to benign prostate hyperplasia (BPH) is progressively demanded by patients and trusted by physicians. The aim was to assess the efficacy of a mix of pumpkin seed extract, soy germ isoflavonoids, and cranberry (Novex®) in the management of mild to moderate LUTS in BPH patients. Male patients aged ≥40 years, who had had mild to moderate LUTS for >6 months at screening, with no previous therapy or who are still symptomatic despite current use of alpha-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Benign Prostate Hyperplasia (BPH) is a progressive pathologic condition associated with elderly men and characterized by proliferation of prostatic tissues, prostate enlargement and consequent lower urinary tract symptoms [1]. These include urinary reluctance, frequent urination, weak stream, and nocturia [2]. Although nearly 70% of men, experience prostate enlargement, after the age of 50, the pathogenesis of BPH is yet to be fully understood [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benign Prostate Hyperplasia (BPH) is a progressive pathologic condition associated with elderly men and characterized by proliferation of prostatic tissues, prostate enlargement and consequent lower urinary tract symptoms [1]. These include urinary reluctance, frequent urination, weak stream, and nocturia [2]. Although nearly 70% of men, experience prostate enlargement, after the age of 50, the pathogenesis of BPH is yet to be fully understood [2].…”
Section: Introductionmentioning
confidence: 99%
“…These include urinary reluctance, frequent urination, weak stream, and nocturia [2]. Although nearly 70% of men, experience prostate enlargement, after the age of 50, the pathogenesis of BPH is yet to be fully understood [2]. Within the transitional zone of the prostate, proliferation of both epithelial and stromal cells occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in 2020, Nemer et al examined a combination treatment of pumpkin seed, isoflavonoids, and cranberry mix in LUTS/BPH subjects in a multicenter open-label one-arm pilot study [ 147 ]. Male patients were recruited, who still had LUTS/BPH symptoms despite current use of alpha-1 blockers, which included 128 men (61.8 + 9.9 years of age).…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%
“…IPSS values significantly decreased from baseline from a value of fifteen compared to 30 days of a score of eleven to 90 days where the IPSS score was nine. QOL values significantly increased from baseline, while HEF-5 levels also improved [ 147 ]. The results suggested that the combination treatment of pumpkin seed extract, soy isoflavones and cranberry relieved LUTS/BPH symptoms in men and had a mild beneficial effect on erectile function.…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%